Human–Asiatic black bear (Ursus thibetanus) interactions in the Kaghan Valley, Pakistan. Issue 5 (3rd September 2018) - Ali, Ashfaq; Waseem, Muhammad; Teng, Mingjun; Ali, Saqib; Ishaq, Muhammad; Haseeb, Abdul; Aryal, Achyut; Zhou, Zhixiang
Abstract : Few studies have reported on the distribution, food choices, general behaviour, and interactions of the Asiatic black bear ( Ursus thibetanus ) with humans. We explored the conservation status of the species and its conflicts with humans in the Kaghan Valley, northwest Pakistan. From September 2013 to December 2015, residents from 24 villages in three major regions of the Kaghan Valley were interviewed about human–bear conflicts. In parallel, a survey for signs of bear presence was conducted to assess bear presence, including bear attacks and crop damage that occurred during the survey period. Most interviewees (70%) confirmed that human–bear conflicts exist, and that they arise primarily from crop raiding ( n = 40), followed by attacks on livestock ( n = 32) and humans ( n = 15). Most interviewees stated that they actively disliked bears (47.3%), or had a generally negative perception of bears (63.3%). Such responses were strongly associated with living close to or within bear habitat. Bears raided approximately 3.8 ha of maize per year, mainly from July to September. Our survey revealed that bears used habitats ranging from dense forest to scrub lands, but preferred steep, high-altitude habitats with dense tree cover. Anthropogenic activities (such as hunting, clear-cutting, expansion of infrastructure, and conversion of forest to agricultural land) were the main causes of conflict between humans and bears. Future studies should collect data on the movement and habitat use of individual bears to facilitate the development of appropriate management strategies to conserve this species effectively. We also recommend training Wildlife Department employees to interact with the local communities to implement acceptable mitigation measures to reduce the currently high conflict levels and thus improve acceptance for bear presence and conservation.